SPS170 : Fundamental of sport management / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course is designed to provide students with basic understanding of effective management strategies. It also provides an understanding of the body of knowledge associated with sport management career opportunities in the sport industry and to sport principles as they apply planning, organizing, leading and controlling skills in relations to sport management.